Ethiopia's high growth and its challenges: Causes and prospects - Jan Priewe (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The paper analyses the enigmatic high growth in Ethiopia from 2004 to 2015 (10.9% p.a.) and gauges the prospects for the future. In 2000, Ethiopia was the poorest country on the globe in per capita GDP - a mere 124 USD in current prices. The main finding is that the take-off was driven by heterodox monetary and fiscal policy which targeted public expenditure for infrastructure. This triggered an increase in domestic demand, reinforced by strongly rising terms of trade under buoyant growth of the global economy until 2008. The combination of favourable factors induced strong productivity leaps mainly in agriculture and lifted millions of smallholder peasants at least partially out of subsistence economy toward participation in markets. Aggressive expansionary macroeconomic policies triggered bulging fixed investment, much beyond a narrow public expenditure boom. Despite two heavy inflation episodes, inflation and the emerging high current account deficit seem under control in 2016. The main downside of the strategy followed by Ethiopian authorities is the unabated appreciation of the real effective exchange rate and the unclear consequences of the past commodity price boom. Tolerated high inflation, mainly due to commodity hikes on the world markets, was not sufficiently offset by nominal depreciation. Despite the stellar achievements in poverty reduction and other developmental goals, the strategy incorporated in the "Growth and Transformation Plan" (GTP) does not sufficiently address the failure of industrialisation, focused on manufacturing. Ethiopia has the third lowest rank in manufacturing as a share of GDP in the group of low-income countries, reaching only half of the average in this group. Without a surge in industrialisation the country is unlikely to find an escalator toward a middle-income economy by 2025 as envisioned in GTP II. This would require a turnaround to direct industrial policy (beyond establishing "industrial parks") and real undervaluation of the currency, which would require a change in monetary policy. A possible alternative route for the medium term could be to further postpone massive industrialisation and correction of the exchange rate and focus intensively on full eradication of poverty and malnutrition. This could unleash productivity gains in agriculture with vast positive external effects. The strategy switch to industrialisation would then come after this phase. We leave the choice of options open in this paper. The prospects of continued very high growth in GTP II seem over-optimistic in face of the slowdown of commodity prices and problems of industrialisation. But good development is not necessarily growth maximisation.
Keywords: O11; O14; O24; O25; O47; O55; 330; economic development; Africa; industrial policy; foreign exchange policy